1971
DOI: 10.1161/01.res.28.5.ii-96
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angiotensin Infusion on Catecholamine Uptake and Reactivity in Blood Vessels

Abstract: The interrelations between angiotensin and catecholamine uptake have been studied in rats. Angiotensin was infused for either 5, 30, or 120 minutes at three dose levels: 1, 12, and 45 ng/kg/min. With short exposures to angiotensin, effects were seen in kidney, uterus, and adrenal gland. These organs had been previously shown to bind the greatest amount of tritiated peptide administered intravenously. In the 5-and 30-minute experiments angiotensin inhibited uptake of either metaraminol or norepinephrine in most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In order to study the direct effects of angiotensin I1 on the kidney the indirect effects of angiotensin I1 which can influence renal function should be avoided or controlled. These effects include an increase in arterial pressure (Page & Helmer, 1940), effects on the central nervous system (Ferrario, Gildenberg & McCubbin, 1972;Severs & Daniels-Severs, 1973), effects on peripheral adrenergic activity (McCubbin & Page, 1963;Khairallah et al, 1971), and stimulation of release of aldosterone by the adrenal gland (Laragh et al, 1960). In the present experiments arterial pressure did not increase when angiotensin I1 was infused directly into the renal artery of dogs and no functional changes took place in the contralateral control kidney.…”
Section: Discussionmentioning
confidence: 45%
“…In order to study the direct effects of angiotensin I1 on the kidney the indirect effects of angiotensin I1 which can influence renal function should be avoided or controlled. These effects include an increase in arterial pressure (Page & Helmer, 1940), effects on the central nervous system (Ferrario, Gildenberg & McCubbin, 1972;Severs & Daniels-Severs, 1973), effects on peripheral adrenergic activity (McCubbin & Page, 1963;Khairallah et al, 1971), and stimulation of release of aldosterone by the adrenal gland (Laragh et al, 1960). In the present experiments arterial pressure did not increase when angiotensin I1 was infused directly into the renal artery of dogs and no functional changes took place in the contralateral control kidney.…”
Section: Discussionmentioning
confidence: 45%
“…Sakurai and Hashimoto 15 and Khairallah et al 12 reported that angiotensin II increased the vasoconstrictor effects of norepinephrine in isolated perfused rabbit ears. The response to norepinephrine of the perfused hindlimbs of rats was observed by Sato and Masuyama 16 to be enhanced by angiotensin II.…”
Section: Discussionmentioning
confidence: 98%
“…Infusions of angiotensin II have been shown to potentiate the vascular effects of sympathetic stimulation or norepinephrine infusion. 12 " 16 Because disturbances of the renal circulation are known to promote renin release, 17 it is possible that the renin-angiotensin system may be involved in the hyperresponsiveness to norepinephrine seen in renal hypertensive animal models.…”
mentioning
confidence: 99%